2002
DOI: 10.1074/jbc.m106649200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Induction of Smooth Muscle Cell Phenotpye Requires Transcriptional and Post-transcriptional Control of Serum Response Factor

Abstract: Transforming growth factor-␤ induces a smooth muscle cell phenotype in undifferentiated mesenchymal cells. To elucidate the mechanism(s) of this phenotypic induction, we focused on the molecular regulation of smooth muscle-␥-actin, whose expression is induced at late stages of smooth muscle differentiation and developmentally restricted to this lineage. Transforming growth factor-␤ induced smooth muscle-␥-actin protein, cytoskeletal localization, and mRNA expression in mesenchymal cells. Smooth muscle-␥-actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 66 publications
4
64
0
Order By: Relevance
“…Up-regulation of smooth muscle proteins by endothelial cell conditioned medium was blocked by preincubation with neutralizing antisera to TGF␤. Subsequent studies showed TGF␤-mediated induction of the late phenotypic marker smooth muscle ␥-actin by means of serum response factor (Hirschi et al, 2002). TGF␤ also induces smooth muscle cell differentiation in both embryonic stem cells (Sinha et al, 2004) and neural crest stem cells (Chen and Lechleider, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of smooth muscle proteins by endothelial cell conditioned medium was blocked by preincubation with neutralizing antisera to TGF␤. Subsequent studies showed TGF␤-mediated induction of the late phenotypic marker smooth muscle ␥-actin by means of serum response factor (Hirschi et al, 2002). TGF␤ also induces smooth muscle cell differentiation in both embryonic stem cells (Sinha et al, 2004) and neural crest stem cells (Chen and Lechleider, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that most SMCspecific differentiation marker genes are dependent on the SRF/myocardin-dependent pathway (Miano, 2003;Wang and Olson, 2004), and that the onset of SRF expression correlates closely with SMC marker expression during development (Browning et al, 1998;Croissant et al, 1996). TGF-␤ induces the expression of SRF, which in turn activates CArG-dependent SMC differentiation (Hirschi et al, 2002;Kawai-Kowase et al, 2004). Furthermore, mouse embryos lacking myocardin die during the early stage of smooth muscle development and fail to express multiple smooth muscle marker genes in embryonic dorsal aorta and other vascular structures .…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor-b (TGF-b) is known to induce the myofibroblast phenotype both in vitro (Desmouliere et al, 1993;Hirschi et al, 2002) and in vivo (Zhou et al, 1996;Sime et al, 1997). We examined the ability of wild-type and mSmile mutant MEF to differentiate into myofibroblasts in response to TGF-b.…”
Section: Myofibroblast Development Is Impaired In Msmile Mutant Embrymentioning
confidence: 99%